Distribution and abundance of dinoflagellates from the coastal waters of Karachi, Pakistan, northern part of the Arabian Sea - Khokhar,F. N. (2022)
Abstract The present study reports on seasonal and spatial variations in diversity, distribution and abundance of dinoflegellates and indicates the presence of HAB species in Pakistan waters. A total of 179 taxa, recorded in this study from offshore and near-shore waters, belong to 41 genera in 26 families and 10 orders. The high species count (149 species) was recorded from Manora Island offshore station (MI-1) and 105 spp, 109 spp and 115 spp were encountered from the Mubarak village offshore station (MV-1), Manora near shore station (MI-2) and Mubarak Village near-shore station (MV-2) respectively. Tripos furca was the dominant and frequently occurring species (> 1 x103 to > 25 x103 cells L-1 from coastal and >1x 105 cells L-l from near-shore stations) in addition to less abundant Alexandrium catenella, Alexandrium sp., Alexandrium minutum, and Prorocentrum micans (>103 to 25x 103cells/L). Another 44 species occurred in relatively low numbers (<103 cell L-l). Seventy species were found throughout the study period at all four stations. High number of species in three genera (Tripos (38), Protoperidinium (34) and Prorocentrum (20) was recorded. Potently toxic (16 genera 43 species) and HAB related (19 genera and 30 species) dinoflagellate taxa were also recorded. The percent contribution of dinoflagellates in total phytoplankton population generally remained below 20% except for a few instances. Manora Island stations had comparatively higher Shannon index and equitability and slightly lower dominance index. The PCA plot showed strong positive correlation among chlorophyll-a concentration, dissolved oxygen, total number of phytoplankton and dinoflagellates.